Review: Jamur Endofit sebagai Biokontrol dan Pemacu Pertumbuhan Tanaman Pangan dan Hortikultura di Lahan Suboptimal - Sari, Jelly Milinia Puspita; Adrian, Rian; Lubis, Raja Bonar (Seminar Nasional Lahan Suboptimal, 2022)
Sari JMP, Adrian R, Lubis RB. 2022. Review: endophytic fungus as biocontrol and growth stimulator of food crops and horticulture in suboptimal land. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober  2022. pp. 722-735. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The productivity of food crops and horticulture in human needs is threatened due to attacks by pests and pathogens with a total global loss around 50 up to 80%. Continuous application of pesticides in control negatively affects pest resistance, pollutes soil, water, biota, also on farmers and consumers health. This review aimed to summarize the potential of endophytic fungi that are useful as biocontrol agents and growth promoters of food and horticulture crops in suboptimal land. It is suspected that endophytic fungi in horticultural crops are the most widely reported as biocontrol agents and plant growth promoters. The scope of this paper is limited to review scientific articles based on data exploration of endophytic fungi (biology, isolation, and identification of endophytic fungi), their biological activities, and growth promoters in increasing crop productivity. Endophytic fungi are important components of plant micro-ecosystems that are widely found in healthy plant tissues such as the genera acremonium, cladosporium, beauveria, metarhizium, muscodor, periconia, ampelomyces, chaetomium, cryptosporiopsis, nodulisporium, penicillium, phomopsis, and others. Endophytic fungi produce excellent metabolites as biocontrol and growth promoting agents such as antibiotics, antivirals, antiprotozoal, antiparasitic, antioxidant, and immunosuppressant compounds that can be utilized for agricultural and food industries. More than 100 species of endophytic fungi have been reported worldwide as biocontrol and plant growth promoters. Based on the literature review, it can be concluded that endophytic fungi have great potential as biocontrol agents and growth promoters of food crops and horticulture in suboptimal land farming in a sustainable manner.